Awarded Public Sculptures - Bi-cycle, Hebei Sculpture Park, China - Antoniou, Klitsa (My University, 2026)
Awarded Public Sculptures - Bi-cycle, Hebei Sculpture Park, China
Keywords: Arts and entertainment